Managing environmental change through inter-agency collaboration: Protective governance in mandated sustainability planning. Issue 125 (November 2021) - An, Brian Y.; Tang, Shui-Yan; Leach, William D.
Abstract: When organizations must collaborate to address resource sustainability dilemmas, concerns about the risk of losing autonomy can dissuade them from joining formal collaborative institutions. We argue that governing rules designed to protect autonomy can entice participation from diverse stakeholders, including underprivileged and often marginalized environmental actors, while enhancing confidence in the collaboration's ongoing and anticipated sustainability efforts. We test this argument in the context of large-scale governance reform in the state of California, which recently mandated local governing entities to collaborate for sustainable groundwater planning or risk state intervention. Using data collected from both archival records and a statewide survey of local groundwater managers, the analysis shows that inclusive representation, unweighted voting power structures, and unanimity decision rules constitute protective governance, which in turn boosts participating agencies' confidence in sustainability efforts. This study provides theoretical and empirical insights into how organizations can address constitutional issues to improve collaborative processes and outcomes of environmental sustainability efforts. Highlights: Collaborative governing rules must protect the autonomy and interests of stakeholders in mandated sustainability planning. Inclusive representation, unweighted voting power structure, and unanimity decision rule contribute to protective governance. Such governing rules enhance collaborative institutions' confidence in the success of joint sustainability planning. Actors joining a collaborative effort must insist on governing rules that grant sufficient power to protect their interests. Designers of environmental mandates should anticipate this need by allowing stakeholders to craft protective governing rules.